2008
DOI: 10.1371/journal.pone.0003533
|View full text |Cite
|
Sign up to set email alerts
|

Strong Signature of Natural Selection within an FHIT Intron Implicated in Prostate Cancer Risk

Abstract: Previously, a candidate gene linkage approach on brother pairs affected with prostate cancer identified a locus of prostate cancer susceptibility at D3S1234 within the fragile histidine triad gene (FHIT), a tumor suppressor that induces apoptosis. Subsequent association tests on 16 SNPs spanning approximately 381 kb surrounding D3S1234 in Americans of European descent revealed significant evidence of association for a single SNP within intron 5 of FHIT. In the current study, re-sequencing and genotyping within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Multiple SNPs in sequences under evolutionary constraint within FHIT intron 5 defined haplotypes with an increased risk of prostate cancer in European‐Americans. The results strongly support the involvement of the FHIT intronic region in an increased risk of prostate cancer [Ding et al, 2008].…”
Section: The Gene and Epigenesupporting
confidence: 82%
“…Multiple SNPs in sequences under evolutionary constraint within FHIT intron 5 defined haplotypes with an increased risk of prostate cancer in European‐Americans. The results strongly support the involvement of the FHIT intronic region in an increased risk of prostate cancer [Ding et al, 2008].…”
Section: The Gene and Epigenesupporting
confidence: 82%
“…Fourteen of 15 tumors (93.3%) with MSI showed MSI in intron 4 or 5 of the FHIT gene in our study, suggesting that introns 4 and 5 are highly unstable. Ding et al [26] recently reported the involvement of the FHIT intronic region in an increased risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This all becomes more important for specific findings, such as the strong signal of selection at the FHIT locus that predisposes to prostate cancer [112]. …”
Section: From Evolutionary Medicine To Evolutionary Molecular Medicinementioning
confidence: 99%